Dampak Kualitas Pelayanan, Citra Perusahaan, dan Kepuasan Nasabah terhadap Loyalitas Konsumen di BMT UGT Sidogiri Cabang Semampir Probolinggo - Alvan Fathony; Saifuddin Saifuddin; Nabila Nabila (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
Faithfulness is a significant resource for each existing company, where this can be a benefit in a competition against companies of similar nature. The focus of the reason for this examination is to figure out how the impact of value in a service, image in the company, and also customer satisfaction on customer loyalty at BMT UGT Sidogiri Indonesia Semampir, Probolinggo partially and simultaneously. Determination of the large or small number of samples, which is carried out using a Slovin, is also determined by approximately 100 respondents utilizing purposive examining strategy and speculation testing is completed through multiple linear regression analysis. Furthermore, the aftereffects of the examination show that the quality or worth of administration and client esteem altogether affect client dependability at BMT UGT Sidogiri, Semampir Probolinggo branch partially and simultaneously. Keywords : Loyalty, Service Quality, Company Image, Customer Satisfaction.